Toxic potential of combined sulforaphane/Pseudomonas aeruginosa mannose sensitive hemagglutinin treatment in cancer patients - Božić, Dragica; Baralić, Katarina; Živančević, Katarina; Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
Sulforaphane (SFN) and Pseudomonas aeruginosa – mannose sensitive hemagglutinin (PA-MSHA) are known immune modulators with shown anti-tumor characteristics and ability to inhibit the growth and progression of cancer cells. However, the benefit/risk ratio of their combinational use is not fully explained and needs further investigation. Thus, this study aims to understand the potential of the given therapy mixture to induce side/toxic effects in cancer patients. With the help of in-depth in silico toxicogenomics analysis, we have previously demonstrated that SFN and PA-MSHA (unpublished data) dysregulated 13 and 64 genes in cancer patients, among which 5 and 16 were repressed, while 8 and 48 were induced by the given molecule, respectively. A total of 21 downregulated and 56 upregulated genes were analyzed with computational tools such as ToppGene ToppFun (https://toppgene.cchmc.org/) and REACTOME (https://reactome.org/PathwayBrowser/#/) to determine the most important Gene Ontology terms and molecular pathways influenced by SFN/PA-MSHA combination. As expected, this therapy approach can lead to dysregulation of cell cycle and p53 signalling pathway, but also acute kidney failure. On the other hand, the set of SFN/PA-MSHA upregulated genes were enriched for leukocyte activation, positive regulation of cell population proliferation, TNF and other cytokines signalling pathways, as well as inflammatory diseases such as psoriasis, ulcerative colitis, or Crohn disease. Thus, the combinational treatment of the given immune modulators might have the potential to cause severe adverse outcomes and should be used with caution in cancer patients with renal insufficiency or immune diseases.